Characterization of CMC and Its Effect on Physical Stability and Shelf Life of Psidium guajava - Arya Avif Alviansyah; Annisa Zahra Ramadhan; Nisrina Azhaar Athaya; Suci Nuraiza; Silvi Permata Defisna; Ibnu Hibban Tasman; Mohammad Khotib (Prodi Kimia, 2025)
Psidium guajava has a high content of vitamin C as an antioxidant that is easily damaged. One way to make it stable with stabilizers in the form of hydrocolloids, which are commonly used is carboxymethyl cellulose (Na CMC). The study aims to determine the effect of CMC addition on guava juice drinks with variations in temperature and storage duration and determine the shelf life. Methods include characterization of CMC (water content, organoleptic and viscosity, pH, NaCl content and purity). Guava juice beverage formulation was made by varying CMC concentration (organoleptic, viscosity, pH and vitamin C content). The best result (0.5% w/b) was continued with temperature treatment of 26°C and 16°C, and observation for 25 days. The results showed that CMC had a purity of 98.54% with NaCl of 1.46% and other results showed that it met the SNI/FAO requirements. The test of CMC addition proved to be able to stabilize the juice based on the viscosity of each treatment, but reduced the level of acidity at 16°C. The 26°C treatment changed color and odor on day 10 while at 16°C it lasted until day 20. Vitamin C content showed that on days 10-15 the treatment stored at 26°C decreased to 0.1 mg/g while at 16°C it was stable until day 25. Determination of shelf life using a mathematical model of degradation kinetics.